Social media marketing gains importance after Covid-19 - Andrew Mason; John Narcum; Kevin Mason (Cogent Business & Management, 2021)
This exploratory research examines how the COVID-19 pandemic led to increases in consumers' social media marketing behaviors in the United States (U.S.). Previous research on the impact of a pandemic has focused on behavior for preventive health, however, little attention has been given to the impact of a pandemic on consumer behaviors. To bridge this gap, the Consumer Decision-Making Model was used as a framework to investigate changes in consumers' social media behaviors as they preform various consumer decision-making processes. More specifically, a questionnaire was used to collect survey data from 327 U.S. consumers. Analysis of Variance tests were performed to examine mean differences in consumers' use of social media as a consumer decision-making tool. The findings showed that consumers have increased their utilization of social media as a tool for identifying products, collecting information on products, evaluating products, and making product purchases. Thus, the findings demonstrate the growing importance of social media marketing since the COVID-19 pandemic began. Given that the COVID-19 pandemic is a global phenomenon, the findings likely can be extrapolated across many nations. Suggestions are provided to help businesses adopt to changes in consumers' social media behaviors as they relate to the consumer decision-making processes.
Keywords: 650; COVID-19; coronavirus; social media; consumer behaviors